Philip Kitcher : Pragmatic Naturalism. - Kaiser, Marie I. (Münstersche Vorlesungen zur Philosophie (Series), 2013)
Philip Kitcher is one of the most distinguished philosophers of our days. He has deeply influenced and inspired many of the debates in the philosophy of biology. Moreover, Kitcher has also made groundbreaking contributions to the philosophy of science in general, to ethics, to the philosophy of religion, to the philosophy of literature, to the philosophy of mathematics, and, most recently, to pragmatism. This volume results from the 15th Münster Lectures in Philosophy with Philip Kitcher. It contains an original article by Kitcher entitled "Pragmatic Naturalism". In addition, it includes eight.